2002
DOI: 10.5650/jos.51.699
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Effects of Randomly Interesterified and Physically Mixed Oils Containing Medium-chain Fatty Acids on Rats.

Abstract: Examination was made of the effects of edible oils containing medium-chain fatty acids (MCFA) on the body fat weight and blood lipid concentrations of rats fed a mixture of randomly interesterified rapeseed oil (87%) and medium-chain triacylglycerols (13%) (MLCT), and a physical mixture of rapeseed oil (87%) and medium-chain triacylglycerols (13%) (MIX). Wistar male rats were randomly divided into three groups and fed diets containing 7% rapeseed oil, MLCT and MIX for 6 weeks. Although the body fat weight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…23,24) However, in our previous study, a physical mixture of LCT and MCT, which contained the same amount of MCFA found in MLCT, showed a significantly lower body fat accumulation than LCT, and that the adipose tissue weight of rats fed MLCT and the physical mixture of LCT and MCT were not significantly different. 8) We suppose that the effect of MLCT on body fat accumulation might not be determined by the structure of MCFA and LCFA within triacylglycerol but rather by the amount of MCFA ingested.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…23,24) However, in our previous study, a physical mixture of LCT and MCT, which contained the same amount of MCFA found in MLCT, showed a significantly lower body fat accumulation than LCT, and that the adipose tissue weight of rats fed MLCT and the physical mixture of LCT and MCT were not significantly different. 8) We suppose that the effect of MLCT on body fat accumulation might not be determined by the structure of MCFA and LCFA within triacylglycerol but rather by the amount of MCFA ingested.…”
Section: Discussionmentioning
confidence: 93%
“…MLCT can replace LCT in the daily diet, and in human and rat studies this replacement has been shown to cause significant lower body fat accumulation. [6][7][8][9][10] Previous studies have suggested possible mechanisms for the effect of MLCT on body fat accumulation, including enhancement of diet-induced energy expenditure in humans 6) and activation of hepatic fatty acid oxidation in rats. 10,11) However, although MLCT contain only oneeighth the amount of MCFA found in MCT, the reasons MLCT cause significant lower body fat accumulation than LCT are still unclear.…”
mentioning
confidence: 99%
“…Also, we previously reported that an intake of 40 g of MCT did not affect liver function or lipid and glucose metabolism, and did not change the accumulation of lipid in the liver (33). 12.1 ± 3.9 0.1 ± 3.6 10.8 ± 3.5 -1.3 ± 3.0 8 12.6 ± 3.7 0.6 ± 3.5 11.9 ± 3.9 -0.2 ± 4.2 12 12.5 ± 3.6 0.5 ± 3.7 12.3 ± 5.1 0.3 ± 3.4…”
Section: Discussionmentioning
confidence: 99%
“…A study using overweight rats found that MCT-fed rats showed a slight decrease of body weight but a great reduction in the size of adipose tissue depots (11). Another study using rats showed that feeding MCT resulted in effective suppression of body fat accumulation compared to feeding LCT (12). However, there are few studies showing a positive effect of MCT intake on body composition in humans.…”
Section: Introductionmentioning
confidence: 99%
“…MLCT contains about 13% MCFA and can readily replace LCT in the daily diet. Additionally, MLCT, compared with LCT, has been shown to cause significantly lower body fat accumulation not only in rats [10][11][12] but also in humans. 13) Our preceding study in rats suggested that the enhanced energy expenditure and MCFA oxidation that was achieved without activating de novo lipogenesis in the liver was at least responsible for the lower body fat accumulation in rats fed with MLCT.…”
mentioning
confidence: 99%